Perlindungan Hukum Terhadap Warga Negara Asing Dalam Pengalihan Obyek Jaminan Fidusia - I Putu Agus Tri Wira Dharma (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
This scientific work is entitled "Legali Protection of Foreign Citizens in the Transfer of Fiduciary Objects". This research uses the normative legali research method. From the results of this study it can be seen that legali protection for third parties, especially Foreign Citizens is not regulated in Law Number 42 of 1999 concerning Fiduciary Guarantees so that Foreign Citizens as third parties do not get legali protection in fiduciary object agreements. However, proper forms given to Foreign Citizens as third parties can take legali actions as regulated in Article 1365 of the Civil Code which is illegali acts to the Debtor, so that the Debtor is obliged to provide compensation to third parties, namely Foreign Citizens